Before I go to sleep : a novel - Watson, S. J. (Steven J.) (New York : Harper, 2011)
An amnesiac attempts to reconstruct her past by keeping a journal and discovers the dangerous inconsistencies in the stories of her husband and her secret doctor.
Keywords: Women authors -- Fiction; Memory disorders -- Fiction; Life change events -- Fiction; Identity (Psychology) -- Fiction; Psychological fiction